Assessment of least-cost pathways for decarbonising Europe's power supply : a model-based long-term scenario analysis accounting for the characteristics of renewable energies - Pfluger, Benjamin (KIT Scientific Publishing, 2013)
This work analyses technological least-cost pathways for deep emission reductions in the European power sector. It seeks a better understanding of the role renewable energies play in the transformation process up to 2050. Therefore, a model is developed which optimises capacity expansion and hourly dispatch of both conventional and renewable power generation, transmission grids and storage facilities in all hours of the analysed years. The model is applied to four long-term scenarios.